1992
DOI: 10.1007/bf00229646
|View full text |Cite
|
Sign up to set email alerts
|

Specific macromolecular interactions between tau and the microtubule system

Abstract: The microtubule-associated protein Tau, a major component of brain microtubules, shares common repeated C-terminal sequences with the high molecular-weight protein MAP-2. It has been shown that tau peptides V187-G204 and V218-G235, representing two main repeats, induced brain tubulin assembly in a concentration-dependent fashion. The specific roles of these repeats in the interaction of tau with microtubules, and its antigenic nature were investigated using synthetic tau peptides and site-directed monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In an attempt to identify Drosophila proteins that may interact with functional domains in tubulin, we subjected the larval high-speed supernatants to affinity chromatography using a column filled with ß1I-(422-434)-tubulin peptide covalently coupled to Sepharose . Previous studies have demonstrated the capacity of this ßl1-tubulin fragment from the C-terminal regulatory domain to interact with MAP-2, MAP-4, and T (Maccioni et al ., 1988;Farfas et al ., 1992) . The proteins adsorbed on the affinity column were selectively eluted with 0.5 M NaCl ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to identify Drosophila proteins that may interact with functional domains in tubulin, we subjected the larval high-speed supernatants to affinity chromatography using a column filled with ß1I-(422-434)-tubulin peptide covalently coupled to Sepharose . Previous studies have demonstrated the capacity of this ßl1-tubulin fragment from the C-terminal regulatory domain to interact with MAP-2, MAP-4, and T (Maccioni et al ., 1988;Farfas et al ., 1992) . The proteins adsorbed on the affinity column were selectively eluted with 0.5 M NaCl ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Microtubule-associated tau protein was purified from fresh bovine brain, following the procedure of Grundke-Iqbal et al (Grundke-Iqbal et al, 1986) with some modifications (Farias et al, 1992). Brain tissue was homogenized at 4°C in 0.1 M Mes buffer, pH 6.8, 1 M glycerol, 1 mM MgCl 2 in a volume equivalent to tissue weight, in the presence of protease inhibitors (10 g/ml pepstatin, 10 g/ml leupeptin, 100 g/ml PMSF and 1 g/ml aprotinin).…”
Section: Purification Of the Microtubule-associated Tau Proteinmentioning
confidence: 99%
“…The microtubular pellets were resuspended in buffer A, and tubulin was puri®ed from the three-cycled microtubular pellets by phosphocellulose chromatography. Tau protein was isolated from brain extracts as described in Farias et al [1992]. MAP-2 was puri®ed as indicated in Vera [1988].…”
Section: Puri®cation Of Proteinsmentioning
confidence: 99%